The significance of analysing potential conflicts in the sales-marketing integration - Hetényi, Gábor; Lengyel, Attila; Szilasi, Magdolna (International Journal of Engineering and Management Sciences, 2019)
Our research aims to identify the critical interfaces between sales and marketing that need to be improved in order to ensure productive cooperation. The relationship between the two departments is full of conflicts and interdependencies. The improvement of communication is of strategical importance, as it is key to staying competitive in the market. The effectiveness and quality of the sales-marketing cooperation is a key factor that is negatively affected by personal and organisational factors as well as a lack of information and conflicts. In addition to the key factors of managing the sales-marketing interfaces, we have also identified the actions that can promote their improvement, including strategic and organisational roles and responsibilities. Our empirical research results show that regular information exchange, more common and interdisciplinary meetings, and a clearly communicated and implemented corporate vision have a positive effect on the coordination and integration of the sales and marketing departments. Consequently, management is reponsible for establishing a corporate vision, i.e. a comprehensive management culture that is clearly communicated across the board in order to increase the employees’ sense of belonging. Of all elements of management culture, the most important factors are coordination and the establishment of a common strategic sysyem. All in all, corporate profit, which is of key importance to the employer, is largely dependent on the successful integration of the sales and marketing departments, which can be achieved through the implementation of the above factors.